Anatomical mapping of the nasal muscles and application to cosmetic surgery. Issue 8 (26th May 2014) - Konschake, Marko; Fritsch, Helga
<x xml:space="preserve">Abstract</x> We present an anatomical mapping of the most important muscles influencing the nose, incorporating constant anatomical structures, and their spatial correlations. At our disposal were the midfaces of 18 bodies of both sexes, obtained by informed consent from body donors aged between 60 and 80 years. Macroscopically, we dissected the nasal regions of eight corpses, six midfaces were prepared according to plastination histology, four by creating plastinated slices. On their way from their periosteal origin to the edge of the skin, the muscles of the nose cross the subcutaneous adipose tissue, dividing it into superficial and deep layers. The individual muscle fibers insert into the skin directly at the reticular corium. Sometimes, they reach the border of the epidermis which represents a special arrangement of corial muscle attachments. The course of the anatomical fibers of individual nasal muscles presented macroscopically and microscopically in this study offers surgeons a detailed overview of the anatomically important muscular landmarks of the midface. Clin. Anat. 27:1178–1184, 2014. © 2014 Wiley Periodicals, Inc.